Multifocal Childhood Cutaneous Tuberculosis: Report of Two Interesting Cases from Sikkim, India. Issue 3 (7th September 2012) - Verma, Shikha; Thakur, Binod Kumar; Gupta, Amlan
<x xml:space="preserve">Abstract</x> Abstract: Cutaneous tuberculosis is an important health problem in developing countries such as India. Poverty, overcrowding, malnutrition, and ignorance are predisposing factors. The commonly seen variants of cutaneous tuberculosis are scrofuloderma, lupus vulgaris, and tuberculosis verrucosa cutis. Malnourished children may present with unusual forms of cutaneous tuberculosis. Herein we report two interesting cases of multifocal cutaneous tuberculosis in malnourished children.